PROFIL GURU PENDIDIKAN JASMANI DI SEKOLAH DASAR PONTIANAK UTARA - Andriani, Nofi; Haetami, Mimi; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThisstudy aims to find out how the profile of physical education teachers at North Pontianak Elementary School. The method used is descriptive method in the form of a survey. The population in this study were all physical education teachers in northern Pontianak and a sample of all physical education teachers in northern Pontianak was obtained. Then the sample of respondents in this study amounted to 45 respondents according to the criteria determined by the researcher. Data collection techniques used are indirect communication techniques and data collection tools in the form of questionnaires. The data analysis technique uses the percentage formula and using SPSS version 22for windows. From the data analysis the researcher found that the teacher profile which includes four teacher competencies consisting of pedagogic competence, professional competence, personality competence and social competence, the results of this study can be categorized as